TMIS:A Decision Support System for Monitoring and Forecasting Prices of Timber Logs - Sivaram, M.; Sandeep, S.; Jinesh, S.; Sujith, K. S.; Rini, G. (Indian Forester, 2016)
The timber market in developing countries is unorganized and there is no proper system available to track the timber market trends. The aim of the study was to develop a computer based decision support system to monitor the timber prices. This system is called as Timber Market Intelligence System (TMIS). In order to monitor the prices of various timber species, timber price indices were constructed using three approaches viz., Laspeyre’s, Pasche’s and Fisher’s Price Index and implemented in TMIS. The price forecast models were also incorporated. The TMIS was demonstrated using the timber price data of Timber Sales Depots of Kerala Forests and Wildlife Department for the period 2005 to 2009. The results indicated that one of the three price index approaches is sufficient to track the teak prices. A simple aggregate price index was found useful in the case of other species Artocarpus hirsutus, Grewia tiliifolia, Xylia xlocarpa, Terminelia paniculata, Terminelia bellirica, Terminelia tomentosa and Largerstroemia microcarpa. The maximum growth in teak prices was observed during the period 2006 to 2007 and only a marginal increase was observed from the year 2008 onwards. The annual growth rate in the prices of teak was lower as compared to other timber species.